Inguinoscrotal bladder herniation: is CT a useful tool in diagnosis? - BALTACIOĞLU, FEYYAZ (My University, 2002)
Urinary bladder herniation into the inguinal canal is a rare occurrence. The condition is often diagnosed during inguinal hernia surgery. We present a rare case of inguinoscrotal bladder herniation with its computed tomography findings.
Keywords: Humans; Middle Aged; Tomography, X-Ray Computed; Male; Diagnosis, Differential; Urinary Bladder Diseases; Hernia, Inguinal; Scrotum